PEMANFAATAN TUMBUHAN PENGHASIL WARNA ALAMI UNTUK TENUN IKAT OLEH SUKU DAYAK IBAN DI DUSUN TEKALONG DAN DUSUN KELAWIK KAPUAS HULU KALIMANTAN BARAT - Lestari, Agil Ayu; Wardenaar, Evy; Mariani, Yeni (Universitas Tanjungpura, 2018)
The utilization of plants as natural dye Â products has long been used by Dayak Iban tribe lives in the Tekalong and Kelawik subvillage. Most of plants is used obtained from the forest surrounding their subvillages. The research uses descriptive methode by observation technique, the data collected with semi structural interview. Based on it the Tekalong and Kelawik subvillages are obtained 3 of the key responden and 18 general responden. There are 22 plants consist of 15 families by Dayak Iban tribe as natural dye source, there are 36 type of colouring result. The natural dyeing process used by Iban tribe are consist of 3 stages, mordanting, extracting and fixation. The products resulted are woven fabric and songket woven fabric, with the kinds of fabric motif from their philosophy. There are consist of fabric, bag and woven scarf, with the price from 90.000 for scarf to 5.000.000 for the woven.Keyword: DayakÂ Iban tribe, Natural Dye and Textile.